Conductometric Estimation of Strong Acid Mixtures using Barium Acetate - Saigal, Bharti; Joshi, G.K.; Khatri, H.K. (Asian Journal of Chemistry, 2010)
The present paper describes conductomeric estimations of strong acid mixtures taking binary systems using barium acetate in presence of large excess of some non-aqueous solvents. The binary systems involved are: (a) H2SO4 + HCl, (b) H2SO4 + HNO3 and the non-aqueous solvents used were acetone and glacial acetic acid. Estimations of H2SO4 in these systems have been found to be most satisfactory. However, estimations of HCl and HNO3 in these systems show some deviations when results are compared with single titrations. A suitable titrant such as lead acetate has also been proposed for the estimation of these binary systems of strong acids.